Literary forecast genre in modern criticism - Govorukhina , Yuliya Anatolyevna; Dmitriyeva , Yuliya Nikolayevna (Жанры речи, 2021)
The article deals with the problem of the genre, which is studied in the theoretical-critical and historicalliterary aspects. The results of the comparative typological analysis of texts containing judgments about the future of literature give ground to talk about the literary forecast as an independent genre and thus update the existing classifications. The genre carriers are the topic, problems, tasks of the critic, as well as the structure of the text, the image of the literature.